Cardiology : - Jablonski, Stanley. (Hanley & Belfus, 2002)
Hanley & Belfus) Spinoff from the Dictionary of Medical Acronyms & Abbreviations, 4th ed., c2001. Pocket-sized text focuses entirely on cardiology terminology. Softcover. DNLM: Cardiology--Abbreviations.